[Des]construções pictóricas transitórias: poética em processo pela ação do desvelamento - Bottene, Sandro (2015)
This proposal in Visual Poetics, developed in the line of research in Art and Visuality, investigates the language of painting and its relationship in the contemporaneity about the transitory aspects, ephemerals and duration, taking into account the symbolic image of the cactus. The object of study occurs through pictorial [de]constructions that provide a visual transformation indicating the passage of time with the performance (or not) of mechanisms or devices that interfere in the physical appearance of the painting, and at the same time, these ones need the accompaniment (attendance) of the process by the action of the artist together at the work. The research period was between 2013 and 2014 and took into account the artistic practices along with the theoretical reflections about the route of my creative process. The acquired results of the research are made up of a succession of stages or different transient pictorial phases that characterize the visuality of poetics. The writing that is said in this dissertation follows arranged by two parts. The first one deals with the [de]construction of poetic with emphasis on the work Inconstant States (2013), respectively, presenting the process of steps, experiments, materials, techniques and even how occurred the idea (research design). Finally, the second part, deals with the extension of poetic starting from the perspective of the deployment of other relevant studies that discuss and deepen this research in Visual Arts.